2014
DOI: 10.4315/0362-028x.jfp-13-470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Deoxynivalenol on Gastric Secretion in Rats

Abstract: Deoxynivalenol (DON) is a common mycotoxin produced by Fusarium sp. in cereals and foods. Ingestion of contaminated foodstuffs can cause digestive disorders in various animals. Many researchers focus on its toxicity and the pathological damage and absorptive function in the intestines. However, the effect of DON on gastric function is still unclear. The objective of the current study was to evaluate the impact of DON on gastric secretion. Rats were gavaged with DON at the dose of 0, 1, 5, and 25 mg/kg of body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…DON has been associated with a spectrum of adverse effects that includes anorexia, growth suppression, emesis, nausea, neuroendocrine changes, and immunosuppression (Pestka, 2010;Pinton and Oswald, 2014). Surprisingly, there are few studies focusing on the histological parameters due to the effects of DON in rats (Abdel-Wahhab et al, 2015;Arnold et al, 1986a;Wang et al, 2014), and no reports have analysed the immunohistochemical changes.…”
Section: Introductionmentioning
confidence: 99%
“…DON has been associated with a spectrum of adverse effects that includes anorexia, growth suppression, emesis, nausea, neuroendocrine changes, and immunosuppression (Pestka, 2010;Pinton and Oswald, 2014). Surprisingly, there are few studies focusing on the histological parameters due to the effects of DON in rats (Abdel-Wahhab et al, 2015;Arnold et al, 1986a;Wang et al, 2014), and no reports have analysed the immunohistochemical changes.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the expression of tight junction proteins claudin-3 and claudin-4 has also been documented for the IPEC-1 cell line when exposed to DON, along with increases in the level of phosphorylated MAPKs ERK 1/2, p38, and JNK proteins [ 20 ]. Furthermore, histological investigations show that DON-exposed piglets experience jejunum villus atrophy and that rats experience significant reductions in gastric secretions and subsequent increases in gut pH when gavaged with DON [ 20 , 33 ]. These negative effects on the gastrointestinal tract collectively lead to secondary-pathogen exposure and decreased nutrient absorption due to increased permeability.…”
Section: Cellular Toxicity Of Donmentioning
confidence: 99%
“…This damage induces an inflammatory response ( Becker et al, 2011 ), leading to digestive dysfunction ( Antonissen et al, 2015 ), slow intestinal transport, and a reduction in intestinal nutrient absorption ( Wache et al, 2009 ; Dietrich et al, 2012 ). Several reports of the toxic effects of DON on the stomach have shown that DON damages the gastric mucosa and inhibits the digestive function of the stomach ( Wang et al, 2014 ; Danicke et al, 2017 ; Serviento et al, 2018 ). However, few studies have reported the toxic injury exerted by DON on the avian glandular stomach.…”
Section: Introductionmentioning
confidence: 99%